Nilai Estetis Religius Tari Baris Kekuwung Di Desa Adat Sandakan - Ida Bagus Gede Bawa Adnyana; I Wayan Mastra; Luh Putu Pancawati (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Balinese culture today is the fruit of a very long historical process. The tracking of the history of Balinese Culture from archeological data shows that the people of Bali have developed their culture since the prehistoric period, namely the era of gathering, hunting, and farming and peaked at Bronze Age. The research used several methods, namely the methods of collecting data, interview and observation. The aim of the research is to find out the religious and aesthetic values of Baris Kekuwung dance. Baris Kekuwung dance serves as Tari Wali, because the dance is sanctified by the community of Sandakan customary village. The dance is only performed in a Balinese Hindu ritual called Mapag Toya at the village’s Masceti temple. The aesthetic values of Baris Kekuwung dance consist of the dance element and the element of its accompanying traditional music or gamelan. The religious values include philosophical values or Tatwa, spiritual values, dharma or truth and the values of rituals and ceremonies. Thus, it is absolute that the deed of humanity must follow the truth as explained in Sarasamuscaya religious. Moreover, the dance was born from the promise or vow of the local community in agriculture, particularly irrigation.